Internamiento en centro gerontológico y sus consecuencias emocionales en un adulto mayor de 70 años de la ciudad de Babahoyo - Pazmiño Vargas, Jessica Mirella (2022)
Through this case study, the emotional consequences of an adult over 70 years of age due to hospitalization in a gerontological center will be evidenced. There are several consequences and in turn the triggers that cause an imbalance in their emotional state and therefore in their quality of life; since on many occasions’ due attention, management and care are not given in relation to age, health status and individual autonomy, either due to ignorance or lack of interest on the part of family members, which in many cases triggers abandonment in these geriatric centers to be cared for by other people. Said internment, in most cases, will increase the risk of worsening their emotional and health status due to distance from their family and social environment, sudden changes in environment, diet, among others. For the execution of this study and data collection, the qualitative and quantitative method will be used, using techniques such as: clinical interview, clinical observation and psychometric tests with the purpose of collecting important patient data.